Faktor Penyebab dan Upaya Penanggulangan Kasus Pembunuhan di Kelurahan Danga, Kecamatan Aesesa, Kabupaten Nagekeo (Deposisi: Jurnal Publikasi Ilmu Hukum, 2023)
The purpose of this research is to analyse the causal factors and efforts to overcome murder cases in Danga Village, Aesesa District, Nagekeo Regency. This type of research is empirical juridical, the approach that the author uses in this research is a qualitative approach. The location of this research is the Nagekeo Resort Police Office. The subjects used as researchers in this study are police officers. The data collection techniques used in this study are interviews, documentation. This research uses a type of qualitative research that produces descriptive data. The results of this study are the criminal act of premeditated murder in the case occurred due to several causative factors, such as unstable emotions, alcoholic beverages, economic factors, low levels of education, revenge factors. The existence of the application of the death penalty Article 340 of the Criminal Code against the perpetrators of the criminal act of premeditated murder which has a very serious capacity and is carried out cruelly, sadistically and truly violates the highest values of humanity. The countermeasures taken against the disclosure of murder cases are Preemtif efforts, namely socialisation, to prevent more severe crimes, the security forces conduct socialisation to the people throughout Indonesia. Furthermore, Repressive efforts are crime scene processing, the authenticity of the place that occurred at the scene of the crime. Finally, the Preventive effort is that the security forces stop the perpetrator's actions so that his behaviour is not repeated again so as not to harm many people or himself.